Trade fragmentation unveiled: five facts on the reconfiguration of global, US and EU trade - Conteduca, Francesco Paolo; Giglioli, Simona; Giordano, Claire; Mancini, Michele; Panon, Ludovic (Economia e politica industriale, 2025)
In this work, we analyse the most recent shifts in trade patterns amid increasing geoeconomic fragmentation. We document five facts about the recent reconfiguration of global, US and EU trade flows. First, a broad retreat from globalization is not taking place. Second, selective decoupling along geopolitical lines is ongoing, and is driven mostly by the weakening of specific trade relationships. Third, while the US dependency on China has been dropping since 2018, for the EU a decline is visible only in 2023, largely driven by few advanced technology products. Fourth, not all dependencies from China are diminishing. US and EU import shares of selected Chinese goods critical for the green transition have indeed even increased. Fifth, US supply chains from China are lengthening, at least for some production lines, as Chinese products increasingly flow through third countries to reach the US market; for the EU it is too early to tell. In general, micro data for Italy indicate that reductions in dependencies from China may be less significant than those emerging from aggregate data, as some EU hubs are increasingly exporting products originated in China to other EU partners such as Italy.